EFEKTIVITAS KEMAMPUAN BERPIKIR KRITIS PADA MATERI SPLDV DENGAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING - Nurlailiya, Triana; Sa'adah, Nihayatus (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Based on the learning objectives according to Permendikbud Number 21 of 2016 and the ability to learn 21st century mathematics critical thinking is one of the focuses of learning at the junior high school level. However, in reality, students' critical thinking skills are still low. This study aims to describe critical thinking skills using the PBL (Problem Based Learning) learning model. This research design uses a posttest only control design. This type of research uses experimental research. Data collection techniques use test methods using posttest sheets. The results of the study concluded that the average posttest value of the critical thinking skills of the experimental class of 78.04 taught using the PBL model is classified as high. While the results of the hypothesis test show that there is an influence of the PBL model on students' critical thinking skills.